The Role of CEO Characteristics in Enhancing Carbon Emission Disclosure: Evidence from Indonesia - Fuadi, Fauzan; Rubihani, Dian; Puspitasari, Selly; Sinatria, Naufal; Pasangka, Praja Habib (Hasanuddin Economics and Business Review, 2024)
This study aims to investigate the influence of CEO characteristics, namely gender, age, and education level, on the disclosure of carbon emissions in manufacturing companies listed on the Indonesia Stock Exchange. Data analysis was conducted through three main stages: classical assumption testing, descriptive statistics, and application of multiple linear regression. This data testing utilized the STATA 14.0 statistical tool to evaluate the influence of CEO characteristics on carbon emissions disclosure. This study's results show that female CEOs, older CEO age, and higher CEO education levels significantly increase corporate carbon emissions disclosure. Female CEOs tend to be more concerned about environmental welfare, while older and highly educated CEOs are more understanding and committed to transparency and corporate social responsibility. This study provides practical implications for companies considering executive characteristics to improve their social performance. In addition, the results also emphasize the importance of gender diversity and investment in education to improve carbon emissions disclosure practices.